Anticarcinogenic potentials of tea catechins - Li, Xiao-Xiang; Liu, Chang; Dong, Shu-Ling; Ou, Can-Song; Lu, Jian-Liang; Ye, Jian-Hui; Liang, Yue-Rong; Zheng, Xin-Qiang (Frontiers in Nutrition, 2022)
Catechins are a cluster of polyphenolic bioactive components in green tea. Anticarcinogenic effects of tea catechins have been reported since the 1980s, but it has been controversial. The present paper reviews the advances in studies on the anticarcinogenic activities of tea and catechins, including epidemiological evidence and anticarcinogenic mechanism. Tea catechins showed antagonistic effects on many cancers, such as gynecological cancers, digestive tract cancers, incident glioma, liver and gallbladder cancers, lung cancer, etc. The mechanism underlying the anticarcinogenic effects of catechins involves in inhibiting the proliferation and growth of cancer cells, scavenging free radicals, suppressing metastasis of cancer cells, improving immunity, interacting with other anticancer drugs, and regulating signaling pathways. The inconsistent results and their causes are also discussed in this paper.